The Conditions and the Mechanism of Students’ Self-Realization in Activity of Small Innovative Enterprises - Yuriy A. Doroshenko; Andrey I. Shutenko; Elena N. Shutenko; Petr I. Ospishchev (International Review of Management and Marketing, 2016)
The aspects of activity of small innovative enterprises established with the participation of university in the charter capital are considered. The essence and the value of students’ self-realization in activity of this enterprise, and also the main conditions of self-realization such as: personal involvement into the innovative activity, realization of the abilities and capacity, social integration into the work process and professional training are disclosed. The personal mechanism of the functioning of small innovative enterprise is set out in the article in two aspects: subjective and normative. The first one covers the attribute signs of students’ self-realization and the relevant principles of the innovative technologies’ application, forming the second imperative component which is above them. Such approach of the solving of the development of the scientific and technological problems of the entrepreneurship in the university infrastructure allows a more adequate integration of the innovative, commercial and personal principles in contemporary higher education.